Post-curing-free platinum catalyst raw rubber and preparation method thereof

By combining the platinum catalyst with mesoporous alumina and other components, a postcurable platinum catalyst raw glue was designed, which solved the problems of reduced activity and poor dispersion of existing platinum catalysts, and achieved high stability and reliability of thermal conductivity.

CN119859414AActive Publication Date: 2025-04-22SHENZHEN BORNSUN IND CO LTD

Patent Information

Application Number
CN202510166123.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-22
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The existing platinum catalysts are easily reduced during storage and use, resulting in a decrease in catalytic activity and poor dispersion and compatibility in silicone thermal glue, which can easily lead to post-curing and affect the service life of electronic components.

Method used

A postcurable platinum catalyst raw gel was designed, and by combining the platinum catalyst with mesoporous alumina, antioxidant, anti-settling agent and dispersant, a catalyst raw gel was formed with excellent oxidation resistance and good dispersion and compatibility in silicone thermal conductivity glue.

Benefits of technology

The modulus and rebound performance of the catalyst raw glue remain stable during the long-term aging process of high temperature, and there is almost no post-curing phenomenon, meeting the application needs of high stability and high reliability of thermal conductivity glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272523050000031
    Figure BDA0005272523050000031
  • Figure BDA0005272523050000051
    Figure BDA0005272523050000051
  • Figure BDA0005272523050000061
    Figure BDA0005272523050000061
Patent Text Reader

Abstract

The invention discloses post-curing-free platinum catalyst original glue which comprises the following components in parts by mass: 5-60 parts of an organosilicon polymer, 0.1-5 parts of a platinum catalyst, 40-65 parts of mesoporous alumina, 0.2-3 parts of an antioxidant, 0.5-8 parts of an anti-settling agent, 0.03-6 parts of a dispersing agent and 3-10 parts of a solvent. The post-curing-free platinum catalyst raw rubber disclosed by the invention is excellent in oxidation resistance and good in dispersity and compatibility in an organosilicon heat-conducting adhesive formula, the modulus and rebound resilience of the material in a high-temperature long-term aging process are kept stable, and a post-curing phenomenon hardly occurs when the post-curing-free platinum catalyst raw rubber is applied to a heat-conducting adhesive formula containing a large amount of heat-conducting filler; the application requirements of high stability and high reliability of the heat-conducting glue are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, and in particular to a non-post-curing platinum catalyst raw rubber and a preparation method thereof. Background Art

[0002] In the field of thermal conductive filling materials for thermal interface gaps of electronic components, addition-type silicone is widely used due to its flexible use, excellent weather resistance, and low processing requirements. It has been extended to a series of silicone system thermal conductive products such as thermal conductive gaskets, thermal conductive silicone gels, and thermal conductive potting compounds. Platinum catalyst is one of the indispensable and important ingredients in the above products, playing a role in catalytic curing.

[0003] In the early days, chloroplatinic acid was used as a catalyst, but due to its low catalytic efficiency, most of the industry currently uses Custer platinum catalyst as a catalyst. During use, Custer platinum catalyst is generally diluted with silicone oil or solvent and then directly added to the formula system and mixed with other components.

[0004] However, the current Custer platinum catalyst is easily exposed to air during storage and addition and use, and is thus partially reduced to platinum, losing its catalytic activity.

[0005] Secondly, the Custer platinum catalyst is complexed on small organic molecules, which has a smaller molecular weight than the silicone oil in the thermal conductive adhesive formula. In addition, the inorganic thermal conductive filler in the thermal conductive adhesive generally accounts for 60-95%. The small molecules of the organic catalyst have a lower density than the inorganic powder filler, and the difference between the liquid and solid phases is large. In the process of pressurized gluing or other production links that require pressurization or natural long-term storage, the organic catalyst is easily separated from the formula system due to its small molecular weight and large difference in density with the inorganic powder filler.

[0006] In addition, in order to pursue high thermal conductivity, the particle size of thermal conductive filler powder used in thermal conductive adhesives is getting larger and larger, and the known particle size range is about 1-200μm. The compatibility of small organic catalyst molecules with inorganic thermal conductive filler powders is poor, and the huge size difference makes it difficult to disperse small molecule catalysts in the system. Large particle size inorganic fillers block the migration and dispersion of catalyst molecules, resulting in local catalyst aggregation and a reduction in local catalyst content.

[0007] Due to the above reasons, the reduced activity or uneven dispersion of ordinary platinum catalysts during the production or application of thermal conductive adhesives will cause the initial cross-linking and curing degree of the silicone thermal conductive adhesive to fail to reach the actual cross-linking degree of the formula ratio, and the initial cross-linking degree is often used to test the applicability of the formula application. After the thermal conductive adhesive is applied to electronic products, it will experience a long-term high temperature environment. The initial uncross-linked part will continue to react and cross-link and cure, and the modulus of the thermal conductive adhesive will continue to increase. This is a post-curing phenomenon. When the modulus of the thermal conductive adhesive increases beyond the set value, it will cause stress damage to electronic components and affect the service life of electronic components. At the same time, the flexibility decreases, the resilience deteriorates, the thermal interface contact decreases, and the heat transfer performance deteriorates.

[0008] Therefore, designing and preparing a catalyst with excellent antioxidant properties, good dispersibility and compatibility in the silicone thermal conductive adhesive formula, and strong pressure resistance can effectively solve the post-curing problem of the thermal conductive adhesive, improve the performance stability of the product modulus and resilience, and meet the high-reliability application requirements of the thermal conductive adhesive. Summary of the invention

[0009] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a platinum catalyst raw rubber without post-curing and a preparation method thereof. The platinum catalyst raw rubber has excellent oxidation resistance and good dispersibility and compatibility in the formula of silicone thermal conductive adhesive.

[0010] The present invention provides the following technical solutions:

[0011] The invention provides a post-curing free platinum catalyst raw rubber, comprising the following components in parts by mass: 5-60 parts of an organosilicon polymer, 0.1-5 parts of a platinum catalyst, 40-65 parts of mesoporous alumina, 0.2-3 parts of an antioxidant, 0.5-8 parts of an anti-settling agent, 0.03-6 parts of a dispersant and 10 parts of a solvent.

[0012] Furthermore, the molecular formula of the platinum catalyst is selected from C 8 H 18 oeLh 2 With Pt(C 3 H 6 SiO) 4 One of them.

[0013] Preferably, the platinum content in the platinum catalyst is 200,000-500,000 ppm.

[0014] Furthermore, the organosilicon polymer is selected from one or a combination of vinyl-terminated polydimethylsiloxane and methyl-terminated polydimethylsiloxane.

[0015] Furthermore, the viscosity of the organosilicon polymer is 50-100000 mPa·s.

[0016] Furthermore, the mesoporous alumina has a median particle size of 1-200 μm and a specific surface area of ​​30-600 m 2 / g, and the total pore volume is 0.1-0.4cm 3 / g.

[0017] Furthermore, the antioxidant is selected from one or a combination of two of 2,6-di-tert-butyl-p-cresol, tert-butylhydroquinone, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)propylenediamine, tris(2,4-di-tert-butylphenyl) phosphite, and bis(2,4-dicumylphenyl)pentaerythritol-diphosphite.

[0018] Furthermore, the anti-settling agent is one of fumed silica and precipitated silica, and the specific surface area of ​​the anti-settling agent is 180-260m 2 / g.

[0019] Furthermore, the molecular structure of the dispersant is as shown in the following formula (1):

[0020]

[0021] Wherein n is 8 to 16, m is 12 to 30, and R is methoxy or ethoxy.

[0022] Furthermore, the solvent is isopropanol or butanol.

[0023] The present application also provides a method for preparing the above-mentioned non-post-curing platinum catalyst raw rubber, comprising the following steps:

[0024] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0025] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 1-12 hours;

[0026] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 40-60° C. for 10-90 min to obtain platinum-alumina particles;

[0027] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, raising the temperature to 90-160° C. and stirring for 0.5-3 h under vacuum conditions to obtain base material 1;

[0028] S5, cooling base material 1 to below 50° C., adding an antioxidant, and continuing to stir under vacuum conditions for 0.5-2 h to obtain base material 2;

[0029] S6. Add platinum-alumina particles to base material 2, and stir for 1-4 hours under vacuum conditions to obtain platinum catalyst raw rubber.

[0030] Through the above scheme design, the present invention has the following effects:

[0031] The non-post-curing platinum catalyst raw glue of the present invention has excellent antioxidant properties, good dispersibility and compatibility in the formula of silicone thermal conductive adhesive, and the modulus and resilience of the material remain stable during long-term aging at high temperature. When used in the formula of thermal conductive adhesive containing a large amount of thermal conductive filler, there is almost no post-curing phenomenon, thus meeting the application requirements of high stability and high reliability of thermal conductive adhesive. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0034] It should also be understood that the terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the appended claims, the singular forms "a", "an" and "the" are intended to include plural forms unless the context clearly indicates otherwise.

[0035] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0036] In addition, the terms "roughly" and "basically" are intended to explain that the relevant content does not require absolute precision, but can have certain deviations. For example, "roughly equal" does not only mean absolute equality. Since it is difficult to achieve absolute "equality" in actual production and operation, there are generally certain deviations. Therefore, in addition to absolute equality, "roughly equal" also includes the above-mentioned situation with certain deviations. Taking this as an example, in other cases, unless otherwise specified, the terms "roughly" and "basically" have similar meanings to the above.

[0037] Example 1

[0038] A non-post-curing platinum catalyst raw rubber comprises the following components in parts by mass: 51.17 parts of an organic silicon polymer, 0.1 parts of a platinum catalyst, 40 parts of mesoporous alumina, 0.2 parts of an antioxidant, 8 parts of an anti-settling agent, 0.03 parts of a dispersant, and 10 parts of isopropanol.

[0039] The organic silicon polymer is vinyl-terminated polydimethylsiloxane with a viscosity of 100000 mPa·s.

[0040] The molecular formula of platinum catalyst is C 8 H 18 oeLh 2 , the platinum content is 300,000 ppm.

[0041] The median particle size of mesoporous alumina is 1 μm and the specific surface area is 600 m 2 / g, and the total pore volume is 0.1cm 3 / g.

[0042] The antioxidant is a combination of 2,6-di-tert-butyl-p-cresol and bis(2,4-dicumylphenyl)pentaerythritol-diphosphite in a ratio of 2:1.1.

[0043] The anti-settling agent is fumed silica with a specific surface area of ​​180m 2 / g.

[0044] The molecular structure of the dispersant is shown in formula (1):

[0045]

[0046] Wherein n is 16, m is 12, and R is ethoxy.

[0047] The preparation method of the original rubber without post-curing platinum catalyst in this embodiment comprises the following steps:

[0048] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0049] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 12 hours;

[0050] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 60° C. for 90 minutes to obtain platinum-alumina particles;

[0051] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, raising the temperature to 90° C. and stirring for 3 h under vacuum conditions to obtain base material 1;

[0052] S5, after lowering the temperature of base material 1 to 40° C., adding an antioxidant, and continuing to stir under vacuum conditions for 0.5 h to obtain base material 2;

[0053] S6. Add platinum-alumina particles to base material 2, and stir for 1 hour under vacuum conditions to obtain platinum catalyst raw rubber.

[0054] Example 2

[0055] A non-post-curing platinum catalyst raw rubber comprises the following components in parts by mass: 20.5 parts of an organic silicon polymer, 5 parts of a platinum catalyst, 65 parts of mesoporous alumina, 3 parts of an antioxidant, 0.5 parts of an anti-settling agent, 6 parts of a dispersant, and 10 parts of isopropanol.

[0056] The organic silicon polymer is vinyl-terminated polydimethylsiloxane with a viscosity of 2000 mPa·s.

[0057] The molecular formula of platinum catalyst is C 8 H 18 oeLh 2 , the platinum content is 200,000 ppm.

[0058] The median particle size of mesoporous alumina is 200 μm and the specific surface area is 30 m 2 / g, and the total pore volume is 0.4cm 3 / g.

[0059] The antioxidant is a combination of tert-butylhydroquinone and tris(2,4-di-tert-butylphenyl) phosphite in a ratio of 1:3.1.

[0060] The anti-settling agent is fumed silica with a specific surface area of ​​260m 2 / g.

[0061] The molecular structure of the dispersant is shown in formula (1):

[0062]

[0063] Wherein n is 8, m is 30, and R is methoxy.

[0064] The preparation method of the original rubber without post-curing platinum catalyst in this embodiment comprises the following steps:

[0065] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0066] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 1 hour;

[0067] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 40° C. for 10 minutes to obtain platinum-alumina particles;

[0068] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, heating to 160° C. and stirring for 0.5 h under vacuum conditions to obtain base material 1;

[0069] S5, after lowering the temperature of base material 1 to 30° C., adding an antioxidant, and continuing to stir under vacuum conditions for 2 h to obtain base material 2;

[0070] S6. Add platinum-alumina particles to base material 2, and stir for 4 hours under vacuum conditions to obtain platinum catalyst raw rubber.

[0071] Example 3

[0072] A non-post-curing platinum catalyst raw rubber comprises the following components in parts by mass: 5 parts of an organic silicon polymer, 2 parts of a platinum catalyst, 50 parts of mesoporous alumina, 1 part of an antioxidant, 3 parts of an anti-settling agent, 5 parts of a dispersant, and 10 parts of isopropanol.

[0073] The organic silicon polymer is vinyl-terminated polydimethylsiloxane with a viscosity of 50000 mPa·s.

[0074] The molecular formula of platinum catalyst is C 8 H 18 oeLh 2 , the platinum content is 300,000 ppm.

[0075] The median particle size of mesoporous alumina is 100 μm and the specific surface area is 100 m 2 / g, and the total pore volume is 0.2cm 3 / g.

[0076] The antioxidant is tert-butylhydroquinone.

[0077] The anti-settling agent is precipitated silica with a specific surface area of ​​220m 2 / g.

[0078] The molecular structure of the dispersant is shown in formula (1):

[0079]

[0080] Wherein n is 12, m is 20, and R is methoxy.

[0081] The preparation method of the original rubber without post-curing platinum catalyst in this embodiment comprises the following steps:

[0082] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0083] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 6 hours;

[0084] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 65° C. for 10 minutes to obtain platinum-alumina particles;

[0085] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, heating to 120° C. and stirring for 1 h under vacuum conditions to obtain base material 1;

[0086] S5, after lowering the temperature of base material 1 to 30° C., adding an antioxidant, and continuing to stir under vacuum conditions for 1 hour to obtain base material 2;

[0087] S6. Add platinum-alumina particles to base material 2, and stir for 2.5 hours under vacuum conditions to obtain platinum catalyst raw rubber.

[0088] Example 4

[0089] A non-post-curing platinum catalyst raw rubber comprises the following components in parts by mass: 60 parts of an organic silicon polymer, 3 parts of a platinum catalyst, 50 parts of mesoporous alumina, 2 parts of an antioxidant, 2 parts of an anti-settling agent, 2 parts of a dispersant, and 10 parts of isopropanol.

[0090] The organic silicon polymer is vinyl-terminated polydimethylsiloxane with a viscosity of 30000 mPa·s.

[0091] The molecular formula of platinum catalyst is Pt(C 3 H 6 SiO) 4 , the platinum content is 400,000 ppm.

[0092] The median particle size of mesoporous alumina is 120 μm and the specific surface area is 200 m 2 / g, and the total pore volume is 0.4cm 3 / g.

[0093] The antioxidant is 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid.

[0094] The anti-settling agent is fumed silica with a specific surface area of ​​260m 2 / g.

[0095] The molecular structure of the dispersant is shown in formula (1):

[0096]

[0097] Wherein n is 10, m is 24, and R is ethoxy.

[0098] The preparation method of the original rubber without post-curing platinum catalyst in this embodiment comprises the following steps:

[0099] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0100] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 8 hours;

[0101] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 45° C. for 50 min to obtain platinum-alumina particles;

[0102] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, heating to 130° C. and stirring for 1.5 h under vacuum conditions to obtain base material 1;

[0103] S5, after lowering the temperature of base material 1 to 30° C., adding an antioxidant, and continuing to stir under vacuum conditions for 2 h to obtain base material 2;

[0104] S6. Add platinum-alumina particles to base material 2, and stir for 3 hours under vacuum conditions to obtain platinum catalyst raw rubber.

[0105] Comparative Example 1

[0106] This comparative example uses a Custer platinum catalyst with a concentration of 3000 ppm.

[0107] Comparative Example 2

[0108] The difference between this comparative example and Example 1 is that the mass fraction of mesoporous alumina is 30 parts.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 1 is that the mass fraction of mesoporous alumina is 70 parts.

[0111] Comparative Example 4

[0112] The difference between this comparative example and Example 1 is that n is 6 and m is 32 in the dispersant.

[0113] Comparative Example 5

[0114] The difference between this comparative example and Example 1 is that n is 18 and m is 10 in the dispersant.

[0115] Comparative Example 6

[0116] The difference between this comparative example and Example 1 is only that the preparation method of the original rubber without post-curing platinum catalyst comprises the following steps:

[0117] S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid;

[0118] S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 12 hours;

[0119] S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 60° C. for 90 minutes to obtain platinum-alumina particles;

[0120] S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, raising the temperature to 90° C. and stirring for 3 h under vacuum conditions, continuing to add the antioxidant and stirring for 0.5 h to obtain a base material;

[0121] S5. Add platinum-alumina particles to the base material and stir for 1 hour under vacuum conditions to obtain platinum catalyst raw rubber.

[0122] Comparative Example 7

[0123] The difference between this comparative example and Example 2 is that the preparation method of the original rubber without post-curing platinum catalyst is carried out under non-vacuum conditions.

[0124] Comparative Example 8

[0125] The difference between this comparative example and Example 1 is that in step S4, the stirring temperature is 80°C.

[0126] Comparative Example 9

[0127] The difference between this comparative example and Example 1 is that in step S4, the stirring temperature is 200° C. and the stirring time is 20 min.

[0128] Comparative Example 10

[0129] The only difference between this comparative example and Example 1 is that the mass fraction of the organosilicon polymer is 3 parts, the mass fraction of the anti-settling agent is 0.2 parts, and the mass fraction of the dispersant is 0.01 parts.

[0130] Comparative Example 11

[0131] The only difference between this comparative example and Example 1 is that the mass fraction of the organosilicon polymer is 60 parts, the mass fraction of the anti-settling agent is 12 parts, and the mass fraction of the dispersant is 0.03 parts.

[0132] Comparative Example 12

[0133] The difference between this comparative example and Example 2 is that the mass fraction of the antioxidant is 0.1 part.

[0134] Comparative Example 13

[0135] The difference between this comparative example and Example 2 is that the antioxidant is 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol).

[0136] The non-post-curing platinum catalyst raw rubber of Examples 1-4 and Comparative Examples 1-13 is used to prepare a thermally conductive gel, and the thermally conductive gel includes the following components in mass fractions: 0.001 parts of the non-post-curing platinum catalyst raw rubber of Examples 1-4 and Comparative Examples 1-13, 1 part of vinyl silicone oil, 0.04 parts of hydrogenated silicone oil, 18 parts of thermally conductive filler, and 0.004 parts of a coupling agent.

[0137] Thermally conductive gels are tested in the following applications:

[0138] (I) Application Test 1

[0139] By mass, 0.001 parts of the original rubber without post-curing platinum catalyst in Examples 1-4 and Comparative Examples 1-13, 1 part of vinyl silicone oil (viscosity of 500mPa·s), 0.04 parts of hydrogenated silicone oil (hydrogen content of 0.3%), 18 parts of thermal conductive filler (alumina mixed with 5 microns and 90 microns, the ratio is 2:3), 0.004 parts of coupling agent (dodecyltriethoxysilane) were uniformly dispersed in a power disperser, and a gel sheet was prepared after vacuum degassing. The initial hardness of the gel sheet was tested, and the modulus and rebound rate after aging in an oven at 160°C for 200H, 500H, and 1000H were tested. The test results are shown in Tables 1 and 2 below.

[0140] Table 1 Application Test 1 Modulus Test Results

[0141]

[0142]

[0143] Table 2 Application test 1 rebound test results

[0144]

[0145]

[0146] (II) Application Test 2

[0147] By mass, 0.001 parts of the original rubber without post-curing platinum catalyst in Examples 1-4 and Comparative Examples 1-13, 1 part of vinyl silicone oil (viscosity of 1000 mPa·s), 0.04 parts of hydrogenated silicone oil (hydrogen content of 0.18%), 11 parts of thermal conductive fillers (3 microns and 40 microns of aluminum oxide, ratio of 1:4), 0.002 parts of coupling agent (dodecyl triethoxysilane) were uniformly dispersed in a power disperser, and a gel sheet was prepared after vacuum degassing. The initial hardness of the gel sheet was tested, and the modulus and rebound rate after aging in an oven at 160°C for 200H, 500H, and 1000H were tested. The test results are shown in Tables 3 and 4 below.

[0148] Table 3 Application Test 2 Modulus Test Results

[0149]

[0150]

[0151] Table 4 Rebound rate test results of application test 2

[0152]

[0153] (III) Application Test 3

[0154] By mass, 0.001 parts of the original rubber without post-curing platinum catalyst in Examples 1-4 and Comparative Examples 1-13, 1 part of vinyl silicone oil (viscosity of 100 mPa·s), 0.04 parts of hydrogenated silicone oil (hydrogen content of 0.1%), 24 parts of thermal conductive fillers (1 micron, 40 micron, 120 micron aluminum nitride, ratio of 1:2:3.5), 0.006 parts of coupling agent (dodecyltrimethoxysilane) were uniformly dispersed in a power disperser, and a gel sheet was prepared after vacuum degassing. The initial hardness of the gel sheet was tested, and the modulus and rebound rate after aging in an oven at 160°C for 200H, 500H, and 1000H were tested. The test results are shown in Tables 5 and 6 below.

[0155] Table 5 Application Test 3 Modulus Test Results

[0156]

[0157]

[0158] Table 6 Resilience test results of application test 3

[0159]

[0160] It can be seen from the above application test results that the platinum catalyst rubber of the present invention is used in the thermal conductive glue formula containing a large amount of thermal conductive fillers, and there is almost no post-curing phenomenon. The modulus and resilience of the material remain stable during the high-temperature long-term aging process, providing reliable and stable protection for the long-term use of electronic components. However, the products prepared directly using the commercially available Custer platinum catalyst or the platinum catalyst rubber obtained by changing the technical solution of the present invention show obvious post-curing phenomenon after high-temperature aging, the modulus increases several times, and the resilience decreases several times, which seriously affects the reliability of the product.

[0161] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A platinum catalyst rubber without post-curing property, characterized in that: The invention comprises the following components in parts by weight: 5-60 parts of organic silicon polymer, 0.1-5 parts of platinum catalyst, 40-65 parts of mesoporous aluminum oxide, 0.2-3 parts of antioxidant, 0.5-8 parts of anti-settling agent, 0.03-6 parts of dispersant and 3-10 parts of solvent.

2. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The molecular formula of the platinum catalyst is selected from C8H 18 One of OPtSi2 and Pt(C3H6SiO)4; the platinum content in the platinum catalyst is 200,000-500,000 ppm.

3. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The organosilicon polymer is selected from one or a combination of vinyl-terminated polydimethylsiloxane and methyl-terminated polydimethylsiloxane.

4. The non-post-curing platinum catalyst raw rubber as claimed in claim 4, characterized in that: The viscosity of the organosilicon polymer is 50-100000 mPa·s.

5. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The mesoporous alumina has a median particle size of 1-200 μm and a specific surface area of ​​30-600 m 2 / g, and the total pore volume is 0.1-0.4cm 3 / g.

6. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The antioxidant is selected from one or a combination of two of 2,6-di-tert-butyl-p-cresol, tert-butylhydroquinone, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, N,N'-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)propylenediamine, tris(2,4-di-tert-butylphenyl) phosphite, and bis(2,4-dicumylphenyl)pentaerythritol-diphosphite.

7. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The anti-settling agent is one of fumed silica and precipitated silica, and the specific surface area of ​​the anti-settling agent is 180-260m 2 / g.

8. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The molecular structure of the dispersant is shown in the following formula (1): Wherein n is 8 to 16, m is 12 to 30, and R is methoxy or ethoxy.

9. The post-curing free platinum catalyst raw rubber as claimed in claim 1, characterized in that: The solvent is isopropanol or butanol.

10. A method for preparing a platinum catalyst rubber without post-curing properties, characterized in that: The following steps are involved: S1, dispersing the platinum catalyst evenly in the solvent to obtain a platinum catalyst solvent liquid; S2, placing the mesoporous alumina into a platinum catalyst solvent solution and soaking it in a vacuum environment for 1-12 hours; S3, taking out the mesoporous alumina, and baking it under vacuum conditions at a temperature of 40-60° C. for 10-90 min to obtain platinum-alumina particles; S4, mixing the organosilicon polymer, anti-settling agent and dispersant uniformly, raising the temperature to 90-160° C. and stirring for 0.5-3 h under vacuum conditions to obtain base material 1; S5, cooling base material 1 to below 50° C., adding an antioxidant, and continuing to stir under vacuum conditions for 0.5-2 h to obtain base material 2; S6. Add platinum-alumina particles to base material 2, and stir for 1-4 hours under vacuum conditions to obtain platinum catalyst raw rubber.

Citation Information

Patent Citations

  • Preparation method for MCM-41 loaded Pt and Al catalyst and application thereof

    CN107376979A

  • Single-component addition type high-temperature-resistant high-thermal-conductivity silica gel and preparation method thereof

    CN112852165A

  • Platinum catalyst and preparation method and application thereof

    CN113262781A

  • Heat-conducting gel with low oil permeability and high reliability and preparation method thereof

    CN115521622A

  • Two-component heat-conducting gel and preparation method thereof

    CN115838535A

Cited By

  • A coated platinum-gold catalyst, its preparation method and use

    CN122878563A